To Achieve Carbon Neutrality, What Do Individual Residents Say? A Case Study of Yunnan Province of China Based on Spatial Analysis - Yang W; Lu Y; Wang L; Xu Y (SAGE Publishing, 2024)
This study aims to explore factors that affect individual residents’ behaviors contributing to reducing carbon emissions (low-carbon behaviors), based on the empirical analysis of the choice of adoption and the extent of adoption of low-carbon practices, such as using low-carbon transportation and energy-saving, in Kunming, China. We use spatial econometric regression models to consider positive spillover of low-carbon behaviors amongst residents as people tend to obtain knowledge and learn good actions from those located nearby. The results show the existence of positive spillover effects of low-carbon behaviors across several types of low-carbon practices. We find that location effects, such as access to parks, residents’ knowledge of carbon neutrality, and science communications in the local community are the most important determinants of residents’ low-carbon behaviors. The findings may provide insights into designing supporting policies to incentivize residents’ low-carbon behaviors and contribute to the pathway toward carbon neutrality from the micro-perspective.
Keywords: carbon-neutral individual; residents; behavioral change; low-carbon behavior; China